Ecological aspects of nitrogen metabolism in plants - Polacco, Joe C. [ (Joe Carmine)] , 1944-; Todd, Christopher D. (John Wiley, 2011)
"Ecological Aspects of Nitrogen Acquisition explores not only how plants compete for nitrogen in complex ecological communities The book also looks in greater detail at the associations plants recruit with other organisms, ranging from soil microbes to arthropods, as nitrogen acquisition strategies, and how these contribute to individual and evolutionary fitness. The book is divided into four sections, each addressing an important set of relationships of plants with the environment and how this impacts the plant?s ability to compete successfully for nitrogen, often the most growth-limiting nutrient. Ecological Aspects of Nitrogen Acquisition provides thorough coverage of this important topic, and will be a vitally important resource for plant scientists, agronomists, and ecologists"